Communities' Satisfaction towards Housing Rehabilitation and Reconstruction Program after September 30, 2009, Earthquake in West Sumatra. (13th April 2016) - Istijono, Bambang; Ophiyandri, Taufika; Chairisna, Diah; Tadzkia, Ade
Abstract : The government of Indonesia had provided the Rehabilitation and Reconstruction (RR) assistance to 194, 636 houses for communities after September 30, 2009, earthquake in West Sumatra. The community-based development model was adopted in this housing program aid. This study aims to explore people's satisfaction towards the RR program and to identify the difference of satisfaction level between urban area and rural area. The research was carried out by conducting a questionnaire survey to 200 communities. The beneficiaries were invited to determine their satisfaction level based on 5 Likert scale from 1 as "not satisfied at all" to 5 as "absolutely satisfied." The satisfaction level was assessed by two factors, process of reconstruction and result of reconstruction. It was found that the level of communities' satisfaction is at average level. The satisfaction level of urban communities is 2.75, while the satisfaction level of rural communities is slightly higher at 2.88. The satisfaction levels of urban and rural communities with the reconstruction process are at 2.63 and 2.75, respectively, while the satisfaction level with the results of the program is at 2.84 and at 2.95, respectively. Communities' satisfaction with the result of reconstruction is higher than that with the process of reconstruction.